HUBUNGAN KINERJA GURU DENGAN MUTU PENDIDIKAN DI SEKOLAH - Fahmi, Agus; Hardiansyah, Hardiansyah; Suryanata, I Made Angga (Jurnal Visionary : Penelitian dan Pengembangan dibidang Administrasi Pendidikan, 2018)
Teacher performance is an important factor in improving the quality of education, especially improving the quality and the quality of education in school can be felt by people ranging from inputs ( input ), the educational process was going on, until the output (output product) of an educational process. Performance good teacher can be seen from a high work commitment, and always able to carry out their duties well and has a high dedication . In the effective performance of teachers and oriented to the quality of education requires a commitment earnestly in quality improvement. the objectives to be achieved in this study are to Know the Teacher Performance Relationship With the quality of education in SMP Negeri 3 Central Praya academic year 2015/2016. Total population in this study were 11 teachers. Data collection methods used in this study is documentation method and questionnaire as the principal method while the method of interview as a complementary method . While the method of data analysis using statistical analysis Product Moment Correlation formula. Based on the calculation formula Product Moment Correlation r hitung results obtained at 0.645 with r tabel value of 0.602 at a significance level of 5 % and N = 11, or ( 0.645 > 0.602 ) . This shows that ( Ho ) is rejected and ( Ha ) is accepted . The conclusion of this research is There a relationship Teacher Performance With Quality of Education in SMP Negeri 3 Central Praya academic year 2015/2016.